Brassinosteroids make plant life easier under abiotic stresses mainly by modulating major components of antioxidant defense system - Vardhini, Bojjam V.; Anjum, Naser A. (Frontiers in Environmental Science, 2015)
Various abiotic stress factors significantly contribute to major worldwide-losses in crop productivity by mainly impacting plant’s stress tolerance/adaptive capacity. The latter is largely governed by the efficiency of antioxidant defense system for the metabolism of elevated reactive oxygen species (ROS), caused by different abiotic stresses. Plant antioxidant defense system includes both enzymatic (such as superoxide dismutase, SOD, E.C. 1.15.1.1; catalase, CAT, E.C. 1.11.1.6; glutathione reductase, GR, E.C. 1.6.4.2; peroxidase, POD, E.C. 1.11.1.7; ascorbate peroxidase, APX, E.C. 1.11.1.11; guaiacol peroxidase, GPX, E.C. 1.11.1.7) and non-enzymatic (such as ascorbic acid, AsA; glutathione, GSH; tocopherols; phenolics, proline etc.) components. Research reports on the status of various abiotic stresses and their impact on plant growth, development and productivity are extensive. However, least information is available on sustainable strategies for the mitigation of abiotic stress-mediated major consequences in plants. Brassinosteroids (BRs) are a novel group of phytohormones with significant growth promoting nature. BRs are considered as growth regulators with pleiotropic effects, as they influence diverse physiological processes like growth, germination of seeds, rhizogenesis, senescence etc. and also confer abiotic stress resistance in plants. In the light of recent reports this paper: (a) overviews major abiotic stresses and plant antioxidant defense system, (b) introduces BRs and highlights their significance in general plant growth and development, and (c) appraises recent literature available on BRs mediated modulation of various components of antioxidant defense system in plants under major abiotic stresses including metals/metalloids, drought, salinity, and temperature regimes. The outcome can be significant in devising future research in the current direction.